A portable ultrasound based screening study on the prevalence and risk factors of cystic echinococcosis in primary school children in East Turkey - Bakal, Unal; Kazez, Ahmet; Akyol, Muammer; Kocakoc, Ercan; Simsek, Sami (Elsevier, 2012)
The tapeworm Echinococcus granulosus constitutes a major public health concern, since its larval stage causes cystic echinococcosis (CE) which is a life-threatening zoonotic disease in many parts of the world. The purpose of the present study was to perform a screening study in order to investigate the prevalence and risk factors of CE using a portable ultrasound (US) in a representative sample of 2500 primary school children aged 7-14 in East Turkey, where CE is known to be endemic. The students were scanned by portable US while standing, with special attention to the liver, spleen, pancreas, and kidneys. The US scan was followed by a physical examination. In addition, a questionnaire was distributed to all students for completion with the assistance of their teachers regarding their demographic and social characteristics as well as their hygienic habits possibly related to CE. Students found positive were subjected to serologic examination. The US based prevalence was 0.2%. Organ involvement was 0.12% for liver and 0.08% for kidney. The response rate of the questionnaire survey was 93%. The risk factors found to be significant (P<0.05) for CE infection were hand washing and family relative with CE. The results of this study indicate that CE infection is an important public health problem in East Turkey requiring appropriate control measures. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Cystic echinococcosis; Ultrasonography; Children; Prevalence; Turkey